Sulfur-containing Secondary Metabolites as Neuroprotective Agents - Venditti, Alessandro; Bianco, Armandodoriano (Current Medicinal Chemistry, 2020)
Sulfur-containing secondary metabolites are a relatively small group of substances of plant origin. The present review is focused on their neuroprotective properties. The results obtained in a series of in vitro and in vivo studies are reported. Among glucosinolates, the wide class of compounds in the sulfur-containing metabolites, glucoraphanin, sulforaphane and isothiocyanates proved to be the more studied in this context and showed interesting properties as modulators of several systems involved in the pathogenesis of neurologic diseases such as oxidative stress, inflammation and apoptosis. Allium sativum L. (garlic) is widely known for its sulfur-containing components endowed with health-promoting activities and its medicinal properties are known from ancient times. In recent studies, garlic components proved active in neuroprotection due to the direct and indirect antioxidant properties, modulation of apoptosis mediators and inhibiting the formation of amyloid protein. Dihydroasparagusic acid, the first dimercaptanic compound isolated from a natural source, effectively inhibited inflammatory and oxidative processes that are important factors for the etiopathogenesis of neurodegenerative diseases, not only for its antioxidant and radical scavenging properties but also because it may down-regulate the expression of several microglial-derived inflammatory mediators. Serofendic acid represents a rare case of sulfur-containing animal-derived secondary metabolite isolated from fetal calf serum extract. It proved effective in the suppression of ROS generation and in the expression of several inflammatory and apoptosis mediators and showed a cytotrophic property in astrocytes, promoting the stellation process. Lastly, the properties of hydrogen sulfide were also reported since in recent times it has been recognized as a signaling molecule and as a mediator in regulating neuron death or survival. It may be produced endogenously from cysteine but may also be released by sulfur-containing secondary metabolites, mainly from those present in garlic.
Keywords: glucosinolates